Genetic Variations of ALDH (rs671) Are Associated With the Persistence of HBV Infection Among the Chinese Han Population - Shang, Dabao; Wang, Peng; Tang, Weiliang; Mo, Ruidong; Lai, Rongtao; Lu, Jie; Li, Ziqiang; Wang, Xiaolin; Cai, Wei; Wang, Hui; Zhao, Gangde; Xie, Qing; et al. (Frontiers in Medicine, 2022)
Alcohol dehydrogenase 1B (ADH1B) and aldehyde dehydrogenase 2 (ALDH2), members of the alcohol dehydrogenase family, have important roles in liver diseases. The roles of the polymorphisms of ADH1B rs1229984 and ALDH2 rs671 in HBV susceptibility and persistent infection were investigated in the present study. Total 1034 hepatitis B patients [99 acute hepatitis B (AHB), 521 chronic hepatitis B (CHB), 158 acute-on-chronic liver failure (ACLF), 159 liver cirrhosis (LC), 97 hepatocellular carcinoma HCC)] and 1262 healthy controls (HC) of Chinese Han population were recruited, and single nucleotide polymorphisms (SNP) of rs671 and rs1229984 were genotyped. Independent and joint roles of rs671 and rs1229984 in HBV infection were analyzed. The results showed that rs671 genotypes had significant different distribution among different subgroups. Compared with HCs, the frequency of rs671-AA genotype was higher in hepatitis B individuals, especially in chronic hepatitis B (CHB) group [adjusted OR (95%CI) =1.899(1.232-2.928), p=0.003, in co-dominant model], which showed significantly positive association. It was further confirmed that CHB individuals carried ALDH2 rs671-AA genotype had higher risk of persistent HBV infection and higher HBV-DNA quantitation compared with those with GG/GA genotype. In addition, rs671-AA genotype might predict HCC incidence in CHB patients. There was no different distributions of alleles or genotypes in rs671 mutant among AHB, ACLF, LC or HCC groups compared with HCs. These data suggested the possible hazardous role of rs671-AA variant in HBV infection and persistence.